Global Hydrogen Trade to Meet the 1.5°C Climate Goal Part II - Technology Review of Hydrogen Carriers (International Renewable Energy Agency, 2022)
The report covers transformation from gaseous hydrogen to a suitable form to allow its transport and storage, its use in the process of transportation itself and its reconversion from the carrier back to pure hydrogen.
Keywords: Hydrogen as fuel.; elektronické knihy; electronic books